2017
DOI: 10.1002/jcb.26487
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of chemotherapy on various biochemical markers in breast cancer patients

Abstract: Chemotherapy is a standard treatment method for the patients with locally advanced breast cancer. Lately, cyclophosphamide (CYP) and doxorubicin (DOX) are used as the major chemotherapeutic agents especially for the treatment of breast cancer. Till date, no serum biomarker has been able to provide an early diagnosis of breast cancer. This study aimed to assess inflammatory, cardiac, renal and hematological markers in 56 breast cancer patients (BCP) before, during and after termination of chemotherapy with CYP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
1
11
2
1
Order By: Relevance
“…By day 14, the mean for the chemotherapy group was significantly higher than the vehicle group ( p < 0.05). IL-6 was significantly higher among the chemotherapy than vehicle groups at all time points (Figure 1D; p < 0.0001), suggesting a sustained effect of chemotherapy on this cytokine, as has been noted in breast cancer patients undergoing doxorubicin plus cyclophosphamide treatment [31]. Altogether, these findings suggest that chemotherapy leads to systemic inflammation, an effect that can be partly moderated by n-3 PUFAs.…”
Section: Resultssupporting
confidence: 71%
“…By day 14, the mean for the chemotherapy group was significantly higher than the vehicle group ( p < 0.05). IL-6 was significantly higher among the chemotherapy than vehicle groups at all time points (Figure 1D; p < 0.0001), suggesting a sustained effect of chemotherapy on this cytokine, as has been noted in breast cancer patients undergoing doxorubicin plus cyclophosphamide treatment [31]. Altogether, these findings suggest that chemotherapy leads to systemic inflammation, an effect that can be partly moderated by n-3 PUFAs.…”
Section: Resultssupporting
confidence: 71%
“…Hematological and biochemical parameters are important indicators in biology and medical research. They are used to judge the health status of animals and thus provide important references in the study of pathology and toxicology and directly and indirectly reflect organ functions [21, 27, 52]. In recent years, as an important animal model, Chinese rhesus macaques have been increasingly used for biomedical research, including disease development, establishment of transgenic animals and stem cells, construction of animal models of diseases, and pre-clinical investigations [5356].…”
Section: Discussionmentioning
confidence: 99%
“…Low levels of adiponectin have been linked to increased BC mortality. 40 Interleukins has been shown by Paz et al 41 to be affected by chemotherapy, as they found that despite IL-6 being increased and IL-10 being decreased compared to controls before treatment; chemotherapy further enhanced this tendency. Another study found no change in interleukins, including IL-6, during adjuvant chemotherapy and/or treatment with aromatase inhibitors.…”
Section: Potential Mechanismsmentioning
confidence: 93%